(untitled) (Ameghiniana, 2013)
A series of ammonite species are described and illustrated from two localities of the Principal Cordillera of Central Chile, where tithonian lo berriasian strata are present, corresponding lo the Baños del Flaco Formation, The Tithonian is represented by Yirgatosphinctes sp. and Substeueroceras koeneni (Steuer) in Arroyo Cruz de Piedra and Windhauseniceras sp. cf. W. internispinosum (Krantz) in Paso Los Bayos, while Cuyaniceras raripartitum (Steuer) and Neocosmoceras sp. cf.N. sayni (Simionescu) from the first locality, andNeocosmoceras sp. cf. N. sayni (Simionescu), Neocomites regularis Leanza, and Thurmanniceras duraznense (Gerth) from the second, are of Upper Berrisian age. The strata show notable different thickness at the two studied localities. This can be explained by a complex palaeogeography, with localized c1asticsupply, although it can also be due to the presence of stratigraphic hiatus.